A DNA Nanocomplex Containing Cascade DNAzymes and Promoter‐Like Zn‐Mn‐Ferrite for Combined Gene/Chemo‐dynamic Therapy. (21st December 2021) - Yao, Chi; Qi, Hedong; Jia, Xuemei; Xu, Yuwei; Tong, Zhaobin; Gu, Zi; Yang, Dayong
Abstract: Sequential control of exogenous chemical events inside cells is a promising way to regulate cell functions and fate. Herein we report a DNA nanocomplex containing cascade DNAzymes and promoter‐like Zn‐Mn‐Ferrite (ZMF), achieving combined gene/chemo‐dynamic therapy. The promoter‐like ZMF decomposed in response to intratumoral glutathione to release a sufficient quantity of metal ions, thus promoting cascade DNA/RNA cleavage and free radical generation. Two kinds of DNAzymes were designed for sequential cascade enzymatic reaction, in which metal ions functioned as cofactors. The primary DNAzyme self‐cleaved the DNA chain with Zn 2+ as cofactor, and produced the secondary DNAzyme; the secondary DNAzyme afterwards cleaved the EGR‐1 mRNA, and thus downregulated the expression of target EGR‐1 protein, achieving DNAzyme‐based gene therapy. Meanwhile, the released Zn 2+, Mn 2+ and Fe 2+ induced Fenton/Fenton‐like reactions, during which free radicals were catalytically generated and efficient chemo‐dynamic therapy was achieved. In a breast cancer mouse model, the administration of DNA nanocomplex led to a significant therapeutic efficacy of tumor growth suppression. Abstract : A DNA nanocomplex containing cascade DNAzymes and promoter‐like Zn‐Mn‐Ferrite was synthesized. The promoter‐like ZMF decomposed in response to intratumoral glutathione to release a sufficient quantity of metal ions, thus promoting cascade DNA/RNA cleavage and free radical generation, and achieving combined gene/chemo‐dynamic therapy.